An In vitro Study Comparing Dimensional Stability of Four Types of Interocclusal Recording Material - Aksshay Shetty; C Mohammed Saleem; B Mohammed Ajmal; S A Saadath Afzaa; Nawal Saleem; Syed A. Raheel (Journal of Pharmacy and Bioallied Sciences)
Background and Objectives: Interocclusal recording materials should have high dimensional stability for accurate articulation. The aim of this in vitro investigation is to assess and compare the linear dimensional stability of interocclusal recording materials over time. Methods: Polyvinylsiloxane, polyether, bisacryl and bite registration wax were used in the study. The test used a mold according to the American Dental Association (ADA) specification number 19. A total of 40 samples were collected, and each group consisted of 10 samples. The dimensional changes in the samples after 1, 24, 48, and 72 h were measured using an optical microscope equipped with a micrometer device. Results: Each sample had five measurements taken at different times, and the mean of those readings was used to calculate the dimensional change and compare it to the initial measurement made on the die. ANOVA and the Tukey HSD test for repeated measurements were used to examine the data. The average percentage dimensional change over time 1) Group A: 1, 24, 48, and 72 h; 2) Group B: 1, 24, 48, 72 h; 3) Group C: 1, 24, 72 h; 4) Group D1, 24, 48, 72 h; and so on. Interpretation and Conclusion: Both material and temporal considerations impact on linear dimensional stability. The most dimensionally stable material was discovered to be polyvinylsiloxane, followed by polyether, bisacryl, and bite registration wax.